Towards a Multifunctional Grammar. ’Language, Reality and Mind’ in a Grammatical Description - Durst-Andersen, Per (HERMES - Journal of Language and Communication in Business, 2017)
Previous grammars of the Russian language are written on the same methodological background and with the same purpose and may therefore be characterized in their entirety. It appears that they (1) are oriented towards the interpretive function, i.e. the hearer, (2) describe the different parts of the grammar in isolation without internal connection, (3) lack a contrastive element and finally (4) incorporate only written sources. In that respect previous grammars fail and cannot live up to what could be called modern standards. Against this background a new type of grammar is proposed -a grammar which (1) takes the speaker into consideration, (2) differentiates three types of “wrongness”, (3) views the Russian language as a specific member of a linguistic supertype which is opposed to two other supertypes, and (4) takes its starting point in speech production, i.e. in oral discourse. After a theoretical discussion several pieces of evidence will be presented in favour of such type of grammar.